Infusion of gliotoxins or a gap junction blocker in the prelimbic cortex increases alcohol preference in Wistar rats - Miguel-Hidalgo, J; Shoyama, Y; Wanzo, V (Journal of psychopharmacology (Oxford), 2009)
Postmortem research has revealed that there is a lower density of glial cells in regions of the prefrontal cortex (PFC) of uncomplicated alcoholics when compared with control subjects. Impairment of astrocyte function in the PFC may contribute to malfunction in circuits involved in emotion- and reward-related subcortical centers, heavily connected with the PFC and directly involved in the pathophysiology of addictive behaviours. The hypothesis was tested that infusion of gliotoxins known to injure astrocytes or of a gap junction blocker into the prelimbic area of the rat PFC results in increased preference for ethanol in rats exposed to free choice between water and 10% ethanol. Fluorocitric acid, L-alpha-aminoadipic acid (AAD) or the gap junction blocker 18-alpha-glycyrrhetinic acid (AGA) were bilaterally infused once into the rat prelimbic cortex and alcohol preference (ratio of 10% ethanol consumed to total liquid ingested) was measured before and after infusion. Infusion of AAD or AGA dissolved in their vehicles, but not of their vehicles alone, resulted in significant transient increase of preference for 10% ethanol. The present data suggest that impaired integrity of glial cells or the gap junctional communication between them in the rat PFC may contribute to changes in ethanol preference.